STRATEGI PEMANFAATAN INSTAGRAM STORY SEBAGAI MEDIA PUBLIKASI KEGIATAN SEKRETARIS DAERAH KOTA BOGOR - Syarifah Noor Zahwa; Hudi Santoso (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of social media has encouraged changes in the pattern of government public communication, including the dissemination of information related to government activities to the public. Instagram has become one of the social media platforms utilized by the government for information publication because it is capable of delivering information quickly, visually, and easily accessible to the public. This study aims to determine the strategy for utilizing Instagram Story as a publication medium for the activities of the Regional Secretary of Bogor City and to identify the supporting and inhibiting factors in its management process. This research employed a qualitative method with a descriptive approach. Data collection techniques were carried out through observation, interviews, and documentation related to the management process of social media publications for the activities of the Regional Secretary of Bogor City. The results of the study indicate that Instagram Story is utilized as a medium for publishing government activities because it is considered capable of delivering information quickly, accurately, and communicatively to the public. The communication strategy applied includes the use of visual content in the form of photos and videos, concise message preparation, and real-time publication of activities. The utilization of Instagram Story also helps build the image of a government that is active and transparent to the public. However, several obstacles were found in the management process, such as time limitations, internet network constraints, and content adjustments to the characteristics of social media audiences.